Insight of patients and their parents into schizophrenia: Exploring agreement and the influence of parental factors. Issue 3 (30th August 2015) - Macgregor, Alexandra; Norton, Joanna; Bortolon, Catherine; Robichon, Melissa; Rolland, Camille; Boulenger, Jean-Philippe; Raffard, Stéphane; Capdevielle, Delphine
Abstract: Poor insight is found in up to 80% of schizophrenia patients and has been associated with multiple factors of which cognitive functioning, social and environmental factors. Few studies have explored associations between patient insight and that of their biological parents׳, and the influence of parental factors. Insight was assessed in 41 patients and their biological parents with Amador׳s Scale for the assessment of Unawareness of Mental Disorder (SUMD). Parents׳ knowledge about schizophrenia and critical attitudes were assessed with validated self-report questionnaires. Both groups underwent cognitive assessments for working memory and executive functioning. Insight in patients and their parents was not associated for any of the SUMD dimensions but a significant correlation was found between patient and parent awareness of treatment effect for patient–parent dyads with frequent daily contact. Low parental critical attitude was associated with higher patient awareness of symptoms and a high parental memory task score with high patient insight. Our study is the first to suggest a possible influence of parental factors such as critical attitudes and cognitive performance on patient insight. Highlights: Association for awareness of treatment effect in patients and parents in daily contact. Association between patient and parent insight not solely based on biological link. Schizophrenia patient insight is associated to biological parents׳ critical attitudes. Schizophrenia patient insight is associated with biological parents׳ cognition. Family interventions in schizophrenia must take into account parents׳ cognition.